Modern Technology’s Effort to Master Time as a Challenge for Ethics - Klun, Branko (Communications - Scientific letters of the University of Zilina, 2017)
Modern technology has been striving to free humans from their subjection to space and time since its very beginnings. Overcoming spatial distances, intrinsically linked to the phenomenon of globalisation, and the parallel process of gaining mastery over time by new means of production and communication, has promised to bring man closer to a fulfilled life. However, instead of giving us more time for an authentic existence, the acceleration of time in modernity (as analysed by sociologist Hartmut Rosa) has led to a chronic lack of time and poses a general question of a good life and ethics. In this article, I intend to refer to Heidegger’s view on the essence of modern technology as an endeavour to win victory over time, and the need of philosophical reflection regarding the positive nature of time. However, authentic time cannot come about without relationships to our fellow humans, and Levinas’ account of temporality will serve as both a correction to Heidegger’s position and a way towards an ethical consideration of time.